The influences of contract structure, contracting process, and service complexity on supplier performance. Issue 4 (28th March 2019) - Zou, Wenting; Brax, Saara A.; Vuori, Mervi; Rajala, Risto
Abstract : Purpose: To build a more comprehensive understanding of factors affecting the success of service contracting, the purpose of this paper is to investigate the influences of service complexity, contract structure and contracting process on the buyer-perceived supplier performance in business-to-business (B2B) services. Design/methodology/approach: A research model is developed based on transaction cost economics and the research on service contracting. The model is tested by the survey data collected. Professional focus groups on LinkedIn are used to generate the list of potential respondents. The sample consists of 177 purchasing professionals from 25 countries. Findings: The results indicate that three major contract dimensions and follow-up management practices positively influence buyer-perceived supplier performance. Furthermore, service complexity amplifies the effects of incentives designed in the contract and the buyer's follow-up contract management on perceived supplier performance. Research limitations/implications: The sample consists of respondents from 25 countries and provides good geographic coverage. However, the results should be generalized with caution because not all countries were represented equally. Practical implications: The study suggests a framework and guidelines for purchasing managers to improve the design and management of service contracts to secure good performance from their supplier. Originality/value: This paper contributes to understanding the performance-enhancing aspects of designing and monitoring service contracts in B2B contexts. It also adds to the knowledge of the role of service complexity in successful B2B service purchasing.